Volatile Components of Haplophyllum canaliculatum Boiss. by Different Extraction Procedures - Nastaran Ahadi; Marzieh Torabbeigi; Zahra Aghaiee Meibodei; Fatemeh Safatian (Journal of Analytical Methods in Chemistry)
Volatile components of Haplophyllum canaliculatum Boiss. grown in Iran were extracted by hydrodistillation (HD), solvent-free microwave extraction (SFME), and headspace solid-phase microextraction (HS-SPME). The components were analyzed by means of GC and GC-MS. The extraction time and temperature for HS-SPME, microwave, power, and exposure time of extraction for SFME were optimized. Twenty-five compounds that represent 99.88% of total compounds in the oil were obtained by the HD method, and the major components for this method were identified as β-pinene (18.90%), 1,8-cineole (13.94%), and piperitone (12.22%). However, piperitone (34.50%), caryophyllene oxide (9.94%), and a-eudesmol were the main compounds among twenty-one constituents, representing 99.89% of the total composition that were characterized in volatiles extracted by the SFME method. Moreover, thirteen compounds, representing 99.95% of the total constituents, were characterized in volatile fraction extracted by the HS-SPME method, which were dominated by β-pinene (21.13%), a-pinene (13.07%), limonene (11.65%), and δ-2-carene (10.23%) as major constituents.